Factors affecting seed predation of Eriotheca gracipiles (Bombacaceae) by parakeets in a cerrado fragment - Francisco, Mercival R.; Lunardi, Vitor O.; Guimaraes, Paulo R.; Galetti, Mauro [UNESP] (Gauthier-villars/editions Elsevier, 2008)
Psittacids are important pre-dispersal seed predators. However, little is known about the parameters that may determine seed predation rates by these birds, such as plants' characteristics and microhabitat. Eriotheca gracilipes (Bombacaceae) is a semi-deciduous tree widely distributed in the Brazilian cerrado. The fruits are dehiscent pods and the seeds are wind-dispersed. Some individuals lose their leaves during the fruiting season, getting very conspicuous. Here we tested the hypothesis that the absence of leaves in E. gracilipes during the fruiting season may increase pre-dispersal seed predation by psittacids. We also tested the hypotheses that (1) seed predation intensity increases with increasing plant size and (2) number of fruits, (3) seed predation decreases with the increasing number of conspecific plants in a range of 15 m, and (4) seed predation intensity is lower in plants with higher vegetation cover over their crowns. The small parakeet Brotogeris versicolurus was the only species observed preying upon the seeds of E. gracilipes. The percentage of fruits damaged by the parakeets ranged from 0 to 100% (66.98 +/- 43.11%, n = 72) among the different plants. Our data give weak support to the hypothesis that the absence of leaves may facilitate plants and/or fruits detection by the parakeets. However, seed predation intensity was significantly affected by crop size. The hypothesis that conspecific fruiting plants surrounding the studied individuals may reduce predation rate was not supported. Nevertheless, trees without higher vegetation cover over their crowns were significantly affected by increased seed predation. This suggests that seed predation by parakeets can be a potential selective factor influencing fruit crop sizes in E. gracilipes. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: Brazil; Brotogeris versicolurus; plant traits evolution; pre-dispersal seed predation; psittacidae